Foraging Activity of Four Bee Species on Sesame Flowers During Two Successive Seasons in Ismailia Governorate, Egypt - mahmoud, mahmoud farag (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Foraging activity of four bee species, Apis mellifera L., Osmia spp., Ceratina tarsata Morawitz and Xylocopa pubescens Spinola on sesame flowers was studied during two successive seasons of 2011 and 2012. Experimental observations were made during four periods of the day: 9:00-11:00 am, 11:00 am-1:00 pm, 1:00-3:00 pm and 3:00-5:00 pm, starting from initial flowering until the final session. Observation time was five minutes during each period and four bee species were observed visiting each square meter area. Five spots of 1 m2 area were selected randomly, and the number of different species of bees visiting was counted for five minutes by using electronic stopwatch, voice recorder and digital video camera. The results of the study indicated that the four bee species were most abundant on sesame flowers between 11:00 am and 1:00 pm, and between 1:00 and 3:00 pm. Among the bees, Apis mellifera was the predominant species, followed by Ceratina tarsata, in the season of 2011, while a reverse order of the two was recorded in 2012. The average time spent per flower was highly significantly different among these four species.